Earl Van Dorn papers - Van Dorn, Earl, 1820-1863.
Letters and telegrams relating to troop movements, supplies and ammunition, the location of enemy gunboats and the capture of prisoners. Sent primarily from Camp Moore, La., Chattanooga, Tenn., and Vicksburg and Jackson, Miss. Includes letters received by Van Dorn while in Mississippi. Correspondents include John C. Breckinridge and Daniel Ruggles.
Confederate army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Breckinridge, John C. -- 1821-1875 -- Correspondence; Ruggles, Daniel, -- 1810-1897 -- Correspondence; Confederate States of America. -- Army; Camp Moore (La.) -- History; Chattanooga (Tenn.) -- History; Jackson (Miss.) -- History -- Civil War, 1861-1865.; Louisiana -- History -- Civil War, 1861-1865.; Mississippi -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Equipment and supplies; United States -- History -- Civil War, 1861-1865 -- Naval operations; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Vicksburg (Miss.) -- History -- Civil War, 1861-1865.; Army officers, Confederate